Vascular function and cholecalciferol supplementation in CKD: A self-controlled case series - Kumar, V; Yadav, A; Singhal, M; Kumar, V; Lal, A; Banerjee, D; Gupta, K; Jha, V (Elsevier, 2018)
Vitamin D deficiency is common and associated with mortality in chronic kidney disease (CKD) patients. Cardiovascular disease (CVD) is the commonest cause of mortality in CKD patients. In a randomized, double blind, placebo controlled trial, we have recently reported favorable effects of vitamin D supplementation on vascular & endothelial function and inflammatory biomarkers in vitamin D deficient patients with non-diabetic stage 3-4 CKD (J Am Soc Nephrol 28: 3100–3108, 2017). Subjects in the placebo group who had still not received vitamin D after completion of the trial received two oral doses 300000 IU of oral cholecalciferol at 8 weeks interval followed by flow mediated dilatation (FMD), pulse wave velocity (PWV), circulating endothelial and inflammatory markers (E-Selectin, vWF, hsCRP and IL-6), 1,25 (OH)2D, iPTH and iFGF-23 assessment at 16 weeks. 31 subjects completed this phase of the study. Last values recorded in the preceding clinical trial were taken as baseline values. Serum 25(OH)D and 1,25(OH)2D increased and FMD significantly improved after cholecalciferol supplementation [mean change in FMD%: 5.8% (95% CI: 4.0-7.5%, p<0.001]. Endothelium independent nitroglycerine mediated dilatation, PWV, iPTH, iFGF-23 and IL-6 also showed favorable changes. The data further cement the findings of beneficial effects of correction of vitamin D deficiency on vascular function.